Narrating the nation and its other: the emergence of Palestine in the postcolonial Arabic novel - Alwadhaf, Yahya Hassan; Omar, Noritah (Penerbit Universiti Kebangsaan Malaysia, 2011)
The Palestinian novel is one of the most neglected, if not totally ignored, genres in postcolonial and postmodern narrative fiction. As a resistant narrative, this literary form aims at creating 'a nation in words' and constructing 'a country in books' since it has disappeared from maps. There are many Palestinian novelists, both males and females, who are struggling for existence in a world totally hostile to them and to their nation. However, it is Ghassan Kanafani (1939-72) who first gave voice to the voiceless and silent people of Palestine. He wrote many novels in which his sole aim was to narrate his nation. This paper evaluates 'Men in the Sun' as a "national" Palestinian form which aims to represent the Palestinian "nation". Taking Anderson (1991) and Bhabha (1990)'s theoretical assumptions about the historical relationship between the nation and the novel into account, we would argue that 'Men in the Sun' represents a Palestinian dream of giving expression to the national longing for a form. Edward Said ' s theory about resistance literature is crucial in this context. The discussion concludes by considering the novel as an example of a narrative of resistance.